2012
DOI: 10.1002/aic.13925
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of dynamic effect in capillary pressure relationship for two‐phase flow in weakly layered porous media

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Well-defined laboratory experiments have been conducted to determine the significance of dynamic effect in capillary pressure relationships for two-phase flow in weakly heterogeneous (layered) porous media. The heterogeneous layers are composed of a fine sand layer sandwiched between two coarse sand layers. Dynamic and quasi-static capillary pressure-saturation (P c -S) and @S/@t-t relationships are determined, which are then used to determine the dynamic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
7
37
1
Order By: Relevance
“…In particular, it has been shown that the heterogeneity in porous media affects the dynamic coefficient significantly by altering the rate to flow equilibrium (Manthey et al 2005;Mirzaei and Das 2007;Sakaki et al 2010;Das and Mirzaei 2013). Das et al (2007) and Das and Mirzaei (2013) show that the dynamic coefficient in heterogeneous domain is higher than in homogeneous domain implying that the two-phase flow system reaches equilibrium earlier in the homogeneous domain at a given water saturation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, it has been shown that the heterogeneity in porous media affects the dynamic coefficient significantly by altering the rate to flow equilibrium (Manthey et al 2005;Mirzaei and Das 2007;Sakaki et al 2010;Das and Mirzaei 2013). Das et al (2007) and Das and Mirzaei (2013) show that the dynamic coefficient in heterogeneous domain is higher than in homogeneous domain implying that the two-phase flow system reaches equilibrium earlier in the homogeneous domain at a given water saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of studies have determined the significance of τ in different circumstances Dahle et al 2005;Manthey et al 2005;Das et al 2007Das et al , 2014Das 2007, 2013;Peszynska and Yi 2008;Juanes 2009;Sakaki et al 2010;Bottero et al 2011;Mumford and O'Carroll 2011;Hanspal and Das 2012;Mirzaei 2012, 2013;Hanspal et al 2013;Hou et al 2014;Zhang et al 2014). In particular, it has been shown that the heterogeneity in porous media affects the dynamic coefficient significantly by altering the rate to flow equilibrium (Manthey et al 2005;Mirzaei and Das 2007;Sakaki et al 2010;Das and Mirzaei 2013). Das et al (2007) and Das and Mirzaei (2013) show that the dynamic coefficient in heterogeneous domain is higher than in homogeneous domain implying that the two-phase flow system reaches equilibrium earlier in the homogeneous domain at a given water saturation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations